Influences of carbon nanotubes on terahertz electromagnetic waves - Liu, Xu. (2013)
The Extraordinary Optical Transmission (EOT) phenomenon, as has been reported by Ebbensen [1], describes the light transmission enhancement through an opaque metal film on condition that the film is regularly patterned with repeating structures, such as two-dimensional (2-D) holes array matrix. The EOT phenomenon is believed to be related to surface plasma on the metal surface. New technologies may be developed based on this phenomenon, which may lead to new types of optical devices.